Pharmacological inhibition of DNA methylation attenuates pressure overload-induced cardiac hypertrophy in rats. (July 2018) - Stenzig, Justus; Schneeberger, Yvonne; Löser, Alexandra; Peters, Barbara S.; Schaefer, Andreas; Zhao, Rong-Rong; Ng, Shi Ling; Höppner, Grit; Geertz, Birgit; Hirt, Marc N.; Tan, Wilson; Wong, Eleanor; et al.
Abstract: Background: Heart failure is associated with altered gene expression and DNA methylation. De novo DNA methylation is associated with gene silencing, but its role in cardiac pathology remains incompletely understood. We hypothesized that inhibition of DNA methyltransferases (DNMT) might prevent the deregulation of gene expression and the deterioration of cardiac function under pressure overload (PO). To test this hypothesis, we evaluated a DNMT inhibitor in PO in rats and analysed DNA methylation in cardiomyocytes. Methods and results: Young male Wistar rats were subjected to PO by transverse aortic constriction (TAC) or to sham surgery. Rats from both groups received solvent or 12.5 mg/kg body weight of the non-nucleosidic DNMT inhibitor RG108, initiated on the day of the intervention. After 4 weeks, we analysed cardiac function by MRI, fibrosis with Sirius Red staining, gene expression by RNA sequencing and qPCR, and DNA methylation by reduced representation bisulphite sequencing (RRBS). RG108 attenuated the 70% increase in heart weight/body weight ratio of TAC over sham to 47% over sham, partially rescued reduced contractility, diminished the fibrotic response and the downregulation of a set of genes including Atp2a2 (SERCA2a) and Adrb1 (beta1-adrenoceptor). RG108 was associated with significantly lower global DNA methylation in cardiomyocytes by 2%. The differentially methylated pathways were "cardiac hypertrophy", "cell death" and "xenobiotic metabolism signalling". Among these, "cardiac hypertrophy" was associated with significant methylation differences in the group comparison sham vs. TAC, but not significant between sham+RG108 and TAC+RG108 treatment, suggesting that RG108 partially prevented differential methylation. However, when comparing TAC and TAC+RG108, the pathway cardiac hypertrophy was not significantly differentially methylated. Conclusions: DNMT inhibitor treatment is associated with attenuation of cardiac hypertrophy and moderate changes in cardiomyocyte DNA methylation. The potential mechanistic link between these two effects and the role of non-myocytes need further clarification. Highlights: Cardiac hypertrophy in rats is associated with altered cardiomyocyte DNA methylation. DNA methylation changes in cardiomyocytes in hypertrophy map to relevant pathways. DNA methyltransferase inhibition in all cell types in hypertrophy partially rescues heart function.